An evaluation of the Swiss staging model for hypothermia using case reports from the literature. Issue 1 (December 2016) - Deslarzes, T.; Rousson, V.; Yersin, B.; Durrer, B.; Pasquier, M.
Abstract Background Core body temperature is used to stage and guide the management of hypothermic patients, however obtaining accurate measurements of core temperature is challenging, especially in the pre-hospital context. The Swiss staging model for hypothermia uses clinical indicators to stage hypothermia. The proposed temperature range for clinical stage 1 is <35-32 °C (95-90 °F), for stage 2, <32-28 °C (<90-82 °F) for stage 3, <28-24 °C (<82-75 °F), and for stage 4 below 24 °C (75 °F). However, the evidence relating these temperature ranges to the clinical stages needs to be strengthened. Methods Medline was used to retrieve data on as many cases of accidental hypothermia (core body temperature <35 °C (95 °F)) as possible. Cases of therapeutic or neonatal hypothermia and those with confounders or insufficient data were excluded. To evaluate the Swiss staging model for hypothermia, we estimated the percentage of those patients who were correctly classified and compared the theoretical with the observed ranges of temperatures for each clinical stage. The number of rescue collapses was also recorded. Results We analysed 183 cases; the median temperature for the sample was 25.2 °C (IQR 22-28). 95 of the 183 patients (51.9 %; 95 % CI = 44.7 %-59.2 %) were correctly classified, while the temperature was overestimated in 36 patients (19.7 %; 95 % CI = 13.9 %-25.4 %). We observed important overlaps among the four stage groups with respect to core temperature, the lowest observed temperature being 28.1 °C for Stage 1, 22 °C for Stage 2, 19.3 °C for Stage 3, and 13.7 °C for stage 4. Conclusion Predicting core body temperature using clinical indicators is a difficult task. Despite the inherent limitations of our study, it increases the strength of the evidence linking the clinical hypothermia stage to core temperature. Decreasing the thresholds of temperatures distinguishing the different stages would allow a reduction in the number of cases where body temperature is overestimated, avoiding some potentially negative consequences for the management of hypothermic patients.